2017
DOI: 10.1111/sji.12516
|View full text |Cite
|
Sign up to set email alerts
|

Association Between TNF‐α Promoter −308 A/G Polymorphism and Systemic Lupus Erythematosus Susceptibility: A Case–Control Study and Meta‐Analysis

Abstract: The tumour necrosis factor-α (TNF-α) promoter -308 A/G polymorphism plays an important role in the aetiology of systemic lupus erythematosus (SLE). Several studies have estimated the association between TNF-α -308 A/G and SLE risk. However, results were inconsistent. A case-control study was carried out to explore the association between TNF-α -308 A/G and the SLE risk in a Chinese Han population. Meta-analysis combining present with previous studies was conducted to further explore the association. Our case-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 49 publications
4
17
0
Order By: Relevance
“…TNF‐α is a proinflammatory cytokine that strongly contributes to inflammatory and immune responses by inducing a cascade of various inflammatory cytokines . Particularly, serum TNF‐α levels appeared increased in SLE patients when compared to healthy controls and they are directly correlated with SLE active disease .…”
Section: Resultsmentioning
confidence: 99%
“…TNF‐α is a proinflammatory cytokine that strongly contributes to inflammatory and immune responses by inducing a cascade of various inflammatory cytokines . Particularly, serum TNF‐α levels appeared increased in SLE patients when compared to healthy controls and they are directly correlated with SLE active disease .…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with the results reported by other authors and confi rm the functional signifi cance of the -308G/А polymorphism. 9,[13][14][15] A difference was found in the secretion of TNF-α in patients with SLE carrying the -1031TT, -1031TС, -863СС, and -863СА genotypes (р=0.009 and р=0.018, respectively). The -1031ТТ and -863СС genotypes lead to a higher secretion of TNF-α compared to the -1031ТС and -863СА genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…The increased inflammatory activity in RA patients was significantly correlated with TNF-α concentrations in serum and synovial fluid of the patients [36,37]. Yang et al showed that TNF-α AA and AG genotypes were associated with SLE susceptibility compared with the GG genotype, and the detected increased risk of lupus nephritis was associated with -308A allele [38]. In addition, Vincent et al study showed that overexpression of the TNF family members, B cell-activating factor (BAFF) and proliferation-inducing ligand (APRIL), correlated with the increased risk of hematologic malignancies in SLE [39].…”
Section: Discussionmentioning
confidence: 99%